How Do People Get Back to Information on the Web? How Can They Do It Better? - Jones, William; Bruce, Harry; Dumais, Susan (Proceedings of Interact 2003, 2003)
In one study, people are observed to keep web information for later use through many different methods including the use of Bookmarks (or Favorites), self-addressed email, hand-written notes, and paper print-outs. Each keeping method realizes its own constellation of important features or functions. No observed method provides all desired functions. .A simple “Add Favorite 2” prototype is developed to support a “super” keeping method designed to realize more functions (reminding, context, multiple points of access) in a single effort. Results were mixed. A second study indicates that people may be increasingly returning to desired web sites using methods that require no explicit keeping behaviour. Especially popular are the use of: 1.) A search service. 2.) Partial completion of a site’s web address (and acceptance of a suggested completion to this address). 3.) The Hyperlinks from another web site. Implications for tool support are explored.